Evaluation of Exercise Tolerance in Non-obstructive Hypertrophic Cardiomyopathy With Myocardial Work and Peak Strain Dispersion by Speckle-Tracking Echocardiography - Su, Ye; Peng, Qionghui; Yin, Lixue; Li, Chunmei (Frontiers in Cardiovascular Medicine, 2022)
Background The aim of this study was to evaluate exercise tolerance in non-obstructive hypertrophic cardiomyopathy (HCM) by investigating the value of myocardial work combined with strain peak dispersion. Methods Sixty-five patients with non-obstructive HCM and with normal left ventricular ejection fraction were enrolled and sixty healthy subjects selected as controls. AFI-two-dimensional ultrasonic speckle tracking technology was used to obtain values for global longitudinal peak strain (GLS), longitudinal strain peak time dispersion (PSD), 18-segment systolic longitudinal peak strain (LPS), 18-segment longitudinal strain peak time (TTPLS), global wasted work (GWW), global constructive work (GCW), global work index (GWI), global work efficiency (GWE) and exercise metabolic equivalent (METS). Results 1) Values for GLS (-17.77% ± 0.20% vs -21.66% ± 0.42%) were lower and PSD (95.10 ± 8.15 ms vs 28.97±1.50 ms) prolonged in HCM patients (p<0.01). 2) An increasing trend was shown in basal segment